HOW HAS THE INDONESIAN STOCK MARKET PERFORMED DURING COVID-19 OUTBREAKS? - Doddy, Setiawan; Taufiq, Arifin; Y Anni, Aryani; Yau, Josephine, Tan Hwang (UNIMAS Publisher, 2021)
This paper analyzes the stock market reaction towards the Covid-19 pandemic by using a sample of Indonesian listed firms. In general, we document a significant negative cumulative abnormal returns when the Indonesian President announces the first case of Covid-19 in Indonesia. This effect remains ten days (weaker) after the announcement. However, we only find a short-term effect on the finance industry. While the explanation is still unclear, the investors may observe that the economic impact on the finance industry may arise in the long-run.